2021
DOI: 10.3847/1538-4357/ac2a36
|View full text |Cite
|
Sign up to set email alerts
|

Big Three Dragons: A [N ii] 122 μm Constraint and New Dust-continuum Detection of a z = 7.15 Bright Lyman-break Galaxy with ALMA

Abstract: We present new Atacama Large Millimeter/submillimeter Array Band 7 observational results of a Lyman-break galaxy at z = 7.15, B14-65666 (“Big Three Dragons”), which is an object detected in [O iii] 88 μm, [C ii] 158 μm, and dust continuum emission during the epoch of reionization. Our targets are the [N ii] 122 μm fine-structure emission line and the underlying 120 μm dust continuum. The dust continuum is detected with a ∼19σ significance. From far-infrared spectral energy distribution sampled at 90, 120, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 107 publications
3
17
0
Order By: Relevance
“…The L([O III] 88 )/SFR ratios of the z > 6 galaxies are comparable to or higher than the local dwarfs, despite their high SFR. These high L([O III] 88 )/SFR ratios at a given SFR are consistent with previous results of higher line-to-L FIR ratios at z > 1 than local line deficit at a given L FIR (e.g., Herrera-Camus et al 2018a;Sugahara et al 2021). The three SMGs exhibit lower L([O III] 88 )/SFR than the other z > 6 galaxies at a given L([C II] 158 )/SFR, implying that SMGs would be analogs of local U/LIRGs, which exhibit lower L([O III] 88 )/SFR than local dwarfs.…”
Section: Fir Sample: Z > 6 Galaxiessupporting
confidence: 92%
See 1 more Smart Citation
“…The L([O III] 88 )/SFR ratios of the z > 6 galaxies are comparable to or higher than the local dwarfs, despite their high SFR. These high L([O III] 88 )/SFR ratios at a given SFR are consistent with previous results of higher line-to-L FIR ratios at z > 1 than local line deficit at a given L FIR (e.g., Herrera-Camus et al 2018a;Sugahara et al 2021). The three SMGs exhibit lower L([O III] 88 )/SFR than the other z > 6 galaxies at a given L([C II] 158 )/SFR, implying that SMGs would be analogs of local U/LIRGs, which exhibit lower L([O III] 88 )/SFR than local dwarfs.…”
Section: Fir Sample: Z > 6 Galaxiessupporting
confidence: 92%
“…The following assumptions are adopted as fiducial models, which partly share the concepts with Nagao et al (2011Nagao et al ( , 2012, Harikane et al (2020b), andSugahara et al (2021). The adopted assumptions are summarized in Table 1.…”
Section: Fiducial Photoionization Modelsmentioning
confidence: 99%
“…The dust emissivities are assumed as β = 1.6 and 2.0. We also compare R0600-ID164 with galaxies at z ; 6 − 7 with normal dust temperatures (40-50 K; shown as green circles) confirmed with ALMA continuum detections in two bands at least, including J1211-0118, J0217-0208 (z = 6.03 and 6.20, respectively; Harikane et al 2020), A1689-zD1 (z = 7.13; Watson et al 2015;Knudsen et al 2017;Inoue et al 2020;Bakx et al 2021), and B14-65666 (z = 7.15;Hashimoto et al 2019;Sugahara et al 2021). Bakx et al (2020) showed that MACS0416 Y1, a lensed galaxy at z = 8.31 (black open squares in Figure 17; also Tamura et al 2019), exhibits abnormally warm dust temperature (T dust >80 K, 90% confidence) and/or steep dust emissivity index (β >2).…”
Section: Gas Depletion Timescalementioning
confidence: 54%
“…We treat B14-65666 as a dust-temperature constrained sample. For our analysis, we use the flux density and the size measurements from Sugahara et al (2021).…”
Section: Datamentioning
confidence: 99%
“…Recently, Inoue et al (2020) (hereafter, I20) developed an alternative and simple analytical approach that enables to derive dust temperatures and IR luminosities using single-band dust continuum observations, dust emission sizes, and dust-to-stellar distribution geometry models. So far, the method is applied to a few examples (I20; Sugahara et al 2021), showing that the method constrains dust temperature of high-redshift galaxies well. In this paper, we further examined the applicability of the method developed in I20, calibrated the model using public data from the ALMA archive, and aimed to provide a simple method to derive dust temperature using single ALMA continuum measurements.…”
mentioning
confidence: 99%